Expansion of recipient‐derived antiviral T cells may influence donor chimerism after allogeneic stem cell transplantation. Issue 6 (19th June 2013) - Borchers, S.; Weissinger, E.M.; Pabst, B.; Ganzenmueller, T.; Dammann, E.; Luther, S.; Diedrich, H.; Ganser, A.; Stadler, M.
Abstract Donor chimerism (DC) analysis is an important marker in the hematopoietic stem cell transplant follow‐up. Here, we present evidence for a possible relationship of infectious complications and declines in DC. We analyzed the DC in patients experiencing cytomegalovirus (CMV) reactivation. In addition, in some patients chimerism analyses of T‐cell subsets were performed. CMV‐specific cytotoxic T‐lymphocytes (CMV‐CTL) were monitored using human leukocyte antigen‐restricted multimer staining. Interestingly, CMV reactivation was accompanied by changes in DC in 11 of 67 patients transplanted. For example, DC declined in a cord blood recipient, in both total leukocytes and CD4 and CD8 T‐cell subsets upon CMV reactivation. The latter was controlled after only 5 days through expanding CMV‐CTL of 96% recipient origin, according to chimerism analysis of CMV‐CTL (enriched beyond 50%). In another patient, transplanted after reduced‐intensity conditioning from a DQB1 mismatched, CMV seronegative donor, incipient CMV reactivation was completely aborted by CMV‐CTL of recipient origin. However, at the same time, mixed chimerism dropped from 51% to 0% donor type, resulting in late graft rejection. Our data indicate that chimerism analyses in subset populations lead to a better understanding of declining total leukocyte chimerism. Furthermore, recipient‐derived CMV‐CTL may be able to control CMV reactivation after reduced‐intensity conditioning. We speculate that autologous CMV‐CTL may be instrumental to overcome recurrent CMV reactivations, especially in patients transplanted from CMV‐seronegative donors. In addition, the expansion of recipient‐derived CMV‐CTL may contribute to both, graft failure or to conversion to full DC.